Nevus depigmentosus/Nevus anemicus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2005)
A single white patch, which is present at birth or from the first period of life, is more frequently nevus depigmentosus. The latter may be more or less extended, sometimes segmental or distributed according to the Blaschko lines. However, also nevus anemicus manifests itself as a white patch at birth or from the first period of life. Some clinical features and some semyology maneuvers help in differentiating the two types of nevi. With regard to the maneuvers, physicians should remember that all the stimuli able to dilate vessels make nevus anemicus more visible.